Mr. Hulot's Invisible Gorilla: Jacques Tati and Inattentional Blindness. Issue 2 (1st June 2021) - Faden, Eric; Mitchel, Aaron; Murph, Alexander; Myers, Taylor; Ryan, Nathan C.
Abstract: This article examines the work of mid-century French filmmaker Jacques Tati. Tati suggested that his films allow more visual freedom to audiences and that audiences discover new material upon multiple viewings of his films. We review the scholarship on Tati, especially in relation to critic André Bazin's theories of realism, and then propose another model for understanding Tati's films: the psychological concept of inattentional blindness. The article then discusses our experiment using eye tracking technology to study how subjects watch Tati's films versus other types of cinema and also how they re-watch films. Finally, we applied several statistical and mathematical tests to the eye tracking data to understand key differences between Tati's films and other filmmaking practices.